Engaging with Intercultural Communicative Competence Discourse in Foreign Language Classroom: Opportunities, Challenges and Way Forward - Sahar, Rafidah (2022)
In recent years there has been a growing interest in the cultural dimension of foreign language education, and teachers today are expected to promote the acquisition of intercultural competence in their learners. In this presentation, I will share a brief analysis of viewpoints on the development of intercultural competence in foreign language teaching classrooms. The analysis is a small part of my engagement with literature reviews of my current research on the appropriate ICC methodology in Malaysian Foreign language classrooms. Specifically, I will discuss the relevance and significance of ICC, highlight some of the challenges faced by instructors and conclude by suggesting ways to go forward in promoting the acquisition of ICC in foreign language classrooms.